Financial Sustainability in US Higher Education Transformational Strategy in Troubled Times - Dumestre, Marcel J. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
This book is a practical approach to insuring financial sustainability of US colleges, presented through the lens of organizational strategic thinking. The book does not simply offer models of how colleges can become financially sustainable in cost cutting, online education, international student recruiting, etc. Rather, it presents a succinct historical perspective of how foundational problems emerged, how some universities transformed themselves, and introduces an organizational strategic thinking process that can be used to develop unique solutions for almost any institution. Marcel J. Dumestre is a retired academic administrator who writes about higher education strategy and philosophy of education. .